The Effect of Glycerol/Water and Sorbitol/Water on the Plasticization of Hydroxyethylacryl Chitosan/Sodium Alginate Films - Pitchaya Treenate; Pathavuth Monvisade; Masayuki Yamaguchi (My University, 2015)
This research aimed to investigate on the effects of glycerol/water and sorbitol/water on the plasticization of hydroxyethylacryl chitosan (HC)/sodium alginate (SA) films. The HC/SA films were prepared with different amount of glycerol or sorbitol as a plasticizer (25, 40 and 50% w/w) and kept at different relative humidity (0% RH and 50% RH) in order to restrict the content of water within the films. The results from differential scanning calorimetry (DSC) showed the miscibility of polymer and plasticizers (glycerol and sorbitol) for all blend compositions. A remarkable reduction of glass transition temperature (Tg) could be obtained by adding glycerol over 40% w/w. For sorbitol plasticized films, although the addition of sorbitol could reduce Tg, it was still higher than room temperature. It was claimed that glycerol could gain more effective plasticizing than sorbitol in the HC/SA films. In the cooperation with water as co-plasticizer (glycerol/water or sorbitol/water), the Tg values of all films were dramatically decreased to -50 °C for glycerol/water plasticized films and down to 0 °C for sorbitol/water plasticized films. The reasonable flexible films could be obtained by the use of either glycerol/water or sorbitol/water as couple plasticizers.
Keywords: Plasticizer; Miscibility; Nanocomposite Films for Food Packaging